2020
DOI: 10.29140/ajal.v3n1.271
|View full text |Cite
|
Sign up to set email alerts
|

A developmental framework for online language teaching skills

Abstract: This article focuses on the need for teachers to develop online skills and describes how experiential, participant focused workshops can change the way in which language teachers can integrate technology into their teaching and help them to successfully implement these 21st century skills. It starts by briefly sketching the development of online language teaching in distance pedagogy and introducing the skills development for teachers and the necessity of online teaching skills before outlining previously deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 7 publications
1
33
0
1
Order By: Relevance
“…Mastering English could be a passport for someone to enter the global world (Rokhyati, 2013). Specifically, in this pandemic era, when the teaching and learning process should be done online, teachers have to develop the skills to successfully integrate digital tools into their classroom practice (Stickler et al, 2020). Thus, technology-aided ELT (English Language Teaching) systems relied on the effectiveness and efficiency of facilitating the teaching and learning process (Mallick et al, 4 3.75%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mastering English could be a passport for someone to enter the global world (Rokhyati, 2013). Specifically, in this pandemic era, when the teaching and learning process should be done online, teachers have to develop the skills to successfully integrate digital tools into their classroom practice (Stickler et al, 2020). Thus, technology-aided ELT (English Language Teaching) systems relied on the effectiveness and efficiency of facilitating the teaching and learning process (Mallick et al, 4 3.75%.…”
Section: Discussionmentioning
confidence: 99%
“…This platform also allows the students to see the questions and all possible answers on their own devices shuffled for each student to keep focusing on doing their own work (Basuki & Hidayati, 2019). Many studies have identified this feature as a positive reinforcement to students and entertaining them during the teaching and learning process (Mohamad et al, 2020;Poudel, 2015;Yanmei et al, 2018)).…”
Section: Quizizzmentioning
confidence: 99%
See 2 more Smart Citations
“…Keperluan guru untuk mengembangkan kemahiran pengajaran dalam talian tidak dapat dinafikan. Oleh itu Stickler et al (2020) menyatakan bagaimana fokus guru kepada bengkel mampu mengubah cara di mana guru bahasa menerapkan teknologi ke dalam pengajaran mereka dan membantu mereka untuk melaksanakan dengan jayanya kemahiran abad ke-21 ini. Model bengkel yang dipersembahkan merupakan tindak balas bagi menangani dengan isu yang digariskan oleh Organisation for Economic Co-operation and Development (OECD) dan juga institusi lain.…”
Section: Pemudahcaraan Dan Pentaksiranunclassified